LITERASI MEDIA DIGITAL DI KOMUNITAS VIDEOGRAPHER âLINKPICTUREIDâ - Abdullah, Ahmad Zakki; Ayuningtyas, Fitria; Uljanatunnisa, Uljanatunnisa (Jurnal Pengabdian Masyarakat AbdiMas, 2018)
AbstractVarious phenomena due to digital media to form a very dynamic user behavior lately. In Indonesia, the legal basis of the ITE Law covers a very narrow and unclear discussion of which of the permissible and unauthorized signs are allowed. This situation is due to the gap between social development with the digital media in everyday life in society. References on the use of digital media is certainly very broad, such as the use for socializing, preaching, announcement, opinion sharing, association, discussion and so forth. In optimizing the use of media certainly needed a socialization and counseling "Literasi Media Digital" in the Community Videographer "LinkPictureID" based creatively. This literacy focuses on millenial generation with focus and locus references, on the scope of production. The interpretation of the locus coverage of the videographer community is called "LinkPictureID" because of the rapidly growing digital video content, and focuses on content content in content processing that explores creative value. The importance of literacy in socialization and counseling is done because videographer usually only understand the application of technical level and do not understand the application of management level or creative value planning. Management is no less important in the implementation of digital media so as to make attractive marketable video products. In the implementation of this literacy participants are expected to optimize the video in digital form and marketed through video channels with google adsense system management as revenue.Â Â Keywords: literacy, media, digitalÂ Abstrak Berbagai fenomena akibat media digital membentuk perilaku pengguna yang sangat dinamis belakangan ini. Di Indonesia, dasar hukum UU ITE mencakup bahasan yang sangat sempit dan kurang jelas mengenai rambu-rambu mana yang diperbolehkan dan mana yang tidak diperbolehkan. Keadaan ini dikarenakan oleh kesenjangan antara perkembangan sosial dengan kaedah media digital pada keseharian di masyarakat. Rujukan mengenai penggunaan media digital tentu sangat luas, seperti penggunaan untuk bersosialisasi, pemberitaan, pengumuman, berbagi opini, pergaulan, diskusi dan sebagainya. Dalam mengoptimalkan penggunaan media tentu diperlukan sebuah sosialisasi dan penyuluhan âLiterasi Media Digitalâ di Komunitas Videographer âLinkPictureIDâ berbasis kreatif. Literasi ini berfokus pada generasi millenial dengan acuan fokus dan lokus, pada cakupan produksi. Penafsiran cakupan lokus pada komunitas videographer bernama âLinkPictureIDâ karena peminatan video di media digital yang semakin pesat, serta fokus pada bahasan konten dalam pengolahan isi yang menggali nilai kreatif. Pentingnya literasi dalam sosialisasi dan penyuluhan ini dilakukan karena videographer biasanya hanya memahami aplikasi tingkat teknis dan tidak paham aplikasi tingkat manajemen ataupun perencanaan nilai kreatif. Manajemen tidak kalah pentingnya dalam implementasi media digital sehingga dapat membuat produk video menarik yang dapat dipasarkan. Dalam implementasi literasi ini peserta diharapkan dapat mengoptimalkan video dalam bentuk digital dan dipasarkan melalui kanal video dengan manajemen sistem google adsense sebagai pendapatan.Â Kata kunci : literasi, media, digital